Coronary Artery Dissection and Perforation Complicating Percutaneous Coronary Intervention A Review - Rahman, Z; Ullah, M; Choudhury, AK (Cardiovascular Journal, 2011)
After its introduction by Andrew R. Gruentzig in 1977 percutaneous coronary intervention (PCI) is widely utilized in the treatment of symptomatic coronary artery disease. Though it has numerous benefits, serious and potentially life-threatening complications of PCI can occur, including iatrogenic coronary artery dissection and perforation. The incidence of these complications has been augmented by the development of coronary interventional devices intended to remove or ablate tissue. Here we review the classification, incidence, pathogenesis, clinical sequelae and management of coronary artery dissection and perforation in the current era due to PCI. Specifically, the current angiographic classifications of coronary artery dissections and perforations are reviewed. The findings of several recent, registries of PCI-related coronary artery perforations and dissection are summarized. The management of coronary artery dissection and perforation is discussed in details, including the application of newer modalities such as covered stents. Keywords: Percutaneous coronary intervention (PCI); Coronary artery dissection DOI: http://dx.doi.org/10.3329/cardio.v3i2.9198 Cardiovasc. J. 2011; 3(2): 239-247